PEMERIKSAAN Escherichia coli dan LARVA CACING PADA SAYURAN LALAPAN KEMANGI (Ocimum basilicum), KOL (Brassica oleracea L. var. capitata. L.), SELADA (Lactuca sativa L.), TERONG (Solanum melongena) YANG DIJUAL DI PASAR TRADISIONAL, SUPERMARKET DAN RESTORAN - Srianna Florensi Purba; Indra Chahaya; Irnawati Marsaulina (Lingkungan dan Kesehatan Kerja, 2013)
Laboratory Analysis to the Content of E. coli and Worm Larvae in Basil(Ocimum basilicum), Cabbage(Brassica oleracea L. var capitata L.), Lettuce (Lactuca sativa L.), Eggplants(Solanum melongena) in Traditional Market, Supermarket and Restaurant in Medan City 2012. Raw vegetables have potential contaminated by human feses with existence of Escherichia coli. Because of it necessary laboratory analisys to the content of bacteria E. coli and worm larvae in raw vegetables. The objective of this research is to know the content of bakteri of E. coli and worm larvae in basil, cabbage, lettuce, and eggplants in traditional market, supermarket and restaurant in Medan city 2012.The method used to survey with descriptive to know the content of bacteria of E. coli and worm larvae in basil, cabbage, lettuce, and eggplants in central market, supermarket and restaurant. The results showed that its found the content of bakteri of E. coli in the traditional market for cabbage, was found 6,2 MPN, supermarket 3 MPN and restaurant 3 MPN, in lettuce it was found in traditional market for 7,2 MPN, supermarket 3 MPN, and restaurant 3 MPN, and in eggplants in traditional market 3 MPN. Whereas, checking on worm larvae in traditional market for lettuce was found Ascaris lumbricoides and in supermarket was found the worm larvae of Trichuris trichiura. It is suggested for those who like to consume raw vegetables should pay attention on the cleanliness of the dish. Key words: Dish of raw vegetables, Escherichia coli, worm larvae